74 Helping non-specialists improve assessment of 'end of life care' phase in structured judgement reviews. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Miller, M; Yates, S; Lowney, AC; Lewis, D
Abstract : Introduction: The Royal College of Physicians introduced National Mortality Case Records Review (NMCRR) programme and the Structured Judgement Review (SJR). Assessment of the 'end of life care phase' in SJRs are often undertaken by a clinician without expertise in palliative medicine. Methods: Criteria were developed in 2019 to guide non specialists in assessing the quality of the 'end of life' phase. 75% of SJRs carried out in OUHFT were reviewed in 2020 - assessing the phase of care score and the text relating to care at the end of life Results: Prior to the introduction of the quality indicators 96% of EOLC was judged good or excellent. Afterward 68% of EoLC was judged good or excellent in keeping with other phases of care. Conclusion: Supporting clinicians by providing quality indicators enabled better assessment of the 'end of life care' phase of SJR. In 2019/20 the distribution of scores is more in line with other domains across the SJR. The scores align with the written information on the SJR forms. Resources: Quality indicators available to all delegates for their use.